STATE RESPONSIBILITY IN THE DISPOSAL OF RADIOACTIVE SUBSTANCES IN THE ASIA-PACIFIC AREA (Case Study on Japanas Disposal of Nuclear Waste in Fukushima Waters) - Annisa Raudlatul Rahmah; Risnain, Muh; Guna Nugraha, Lalu (Mataram Journal of International Law, 2024)
This research aims to find out and examine Japan's responsibility for disposing of radioactive waste in the waters of the Asia Pacific region and to find out and understand the steps that the IAEA should take in resolving the disposal of radioactive waste in the waters of the Asia Pacific region by Japan. This research method uses a type of normative legal research, namely by taking a conceptual approach and a case approach. The actions taken by Japan give rise to responsibilities that must be fulfilled because they violate obligations in several principles and provisions of international law. Actions in disposing of radioactive by Japan have received approval from the IAEA because the level or content of radioactive waste disposed of by Japan is still classified as safe as per the results of laboratory research carried out by TEPCO and the IAEA.